A Review of Animal and Human Studies for Management of Benign Prostatic Hyperplasia with Natural Products: Perspective of New Pharmacological Agents - Azimi, Hanieh; Khakshur, Ali-Asghar; Aghdasi, Iman; Fallah-Tafti, Mehrnaz; Abdollahi, Mohammad (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
objective: In this paper, we reviewed plants being effective in treatment of BPH for the purpose of finding new sources of pharmaceutical agents. Methods: All pertinent literature databases were searched. The search keywords were plant, herb, herbal therapy, phytotherapy, benign prostatic hyperplasia, BPH, and prostate. All of the human, animal and in vitro studies were evaluated. Results: According to the studies, some of the substantial effective constituents of the plants in treatment of BPH are oenothein B, icaritin, xanthohumol, diarylheptanoid, 2,6,4'-trihydroxy-4-methoxybenzophenone, emodin, fatty acids, atraric acid, n-butylbenzene-sulfonamide, curbicin, theaflavin-3,30-digallate, penta-O-galloyl-b-D-glucose, lycopene, sinalbin, β-sitosterol, secoisolariciresinol diglucoside, genistein, apigenin, baicalein, and daidzein. Besides, Serenoa repens, Pygeum africanum, Curcubita pepo, and Urtica dioica as the most prevalent plants used to treat BPH. S. repens in human studies showed equivalent effectiveness to tamsulosin and in combination to U. dioica revealed equal effects to finastride with less side effects. Conclusion: There are numerous plants that have beneficial influence on BPH although the mechanisms of action in some plants are not well understood yet. Active ingredients of some of these plants are known and can be used as lead components for development of new effective and safe drugs.
Keywords: animal